Effectiveness of Samapta Unit Dialogical Patrol in Preventing the Crime of Theft with Aggravation in the Jurisdiction of Sidoarjo Polresta - Prasetya, Irfan Mulia (Advances in Police Science Research Journal, 2024)
The crime of theft with weighting is increasing and growing rapidly from 2021 to 2023. The problem formulation in this writing is 1) How is it implemented Dialogic patrol of the Samapta Unit in preventing criminal acts of theft with weights in Sidoarjo Police jurisdiction? 2) What factors influence the implementation of dialogical patrols Samapta Unit in preventing criminal acts of theft with weights in the jurisdiction Sidoarjo Police? 3) What are the efforts to increase the effectiveness of the internal Samapta Unit’s dialogue patrols? prevention of criminal acts of theft with weights in the jurisdiction of the Sidoarjo Police? Objective This research is to describe and analyze the implementation of dialogic patrol efforts increasing the effectiveness of dialogical patrols and explaining what influencing factors. This research uses a qualitative approach because the researcher wants to research comprehensively in depth about the effectiveness of Dialogical Patrols of the Samapta Unit Patrol Unit in preventing cheating in Sidoarjo Police Legal Area. The type of research used is field research with make direct observations in the field. Data collection techniques use observation, interviews, and document studies. The results of the research show the implementation of dialogue patrols by the Sidoarjo Police Samapta Unit still not effective. This is due to several things, such as during the implementation of the patrol it was discovered: discrepancies in several administrations, the number of four-wheeled vehicles (R4) that need to be updated and plus, the number of personnel does not comply with the DSP (Personnel Composition List), and the lack thereof Use of technology for patorli. The next influencing factor is the ability factor from members who have not been dikbang and dikjur, factors of damaged motor vehicles, as well as factors from lack of budget for fuel oil. Improvement efforts are carried out in coordination with other units and agencies.